In search for effective methods of routine formation = W poszukiwaniu skutecznych metod kształtowania rutyn organizacyjnych - Kandora, Marcin (Zielona Góra: Faculty of Economics and Management Press)
Organizational routines are a frequently researched phenomenon in contemporary management science. Although the available theoretical foundations of Routine Theory seem to have reached a significant degree of maturity over the last thirty years, the same could not be said about the availability of material advice for the management practice.
Keywords: rutyny organizacyjne; integracja aplikacji; implementacja rutyn; organizational routines; application integration; routine implementation; controlled learning